(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The current global trend towards electric vehicles is growing as governments and automobile manufacturers are focusing on agendas such as “going green”, fighting climate change etc. The electric vehicle design is a core part for these. The Electric vehicles themselves run on electrical energy derived from an energy source, commonly batteries. These batteries need to be charged. For this purpose, a charging station needs to be provided. The charging stations or points convert the energy available to them through various sources to electrical energy in DC form for the vehicle. These chargers have to be able to accept user input, such as the amount of power to be delivered, such that the user can pay for as per requirement. In this paper a solar charging station with a local battery reserve is simulated for charging of an electric vehicle. This simulation lays the ground work for solar based designs for Electric Vehicle (EV) chargers.